High-performance Ti-doped O3-type Na[Ti-x(Ni0.6Co0.2Mn0.2)(1-x)]O-2 cathodes for practical sodium-ion batteries - Yu, Tae-Yeon; Hwang, Jang-Yeon; Bae, In Tae; Jung, Hun-Gi; Sun, Yang-Kook (ELSEVIER SCIENCE BV, 2019)
Ti-doped O3-type Na[Ti-x(Ni0.6Co0.2Mn0.2)(1-x)]O-2 is studied as a high-performance cathode material for practical sodium-ion batteries. The effect of partial Ti doping on the structural and electrochemical properties of O3-type Na[Ni0.6Co0.2Mn0.2]O-2 materials is investigated by varying the Ti content (x) in Na[Ni0.6Co0.2Mn0.2]O-2 from 0 to 0.01 to 0.03. Scanning electron microscopy images show that upon doping, the primary particles aggregate and form densely packed secondary particles, yielding enhanced mechanical strength and high tap density of similar to 2.3 g cm(-3). The compact morphology of the particles effectively minimizes the void volume for possible electrolyte penetration that usually leads to unwanted side reactions. In addition, partial doping of Ti in the transition-metal layer greatly Improve the structural stability. By taking both morphological and structural advantages, the O3-type Na[Ti-0.03(Ni0.6Co0.2Mn0.2)(o.97)]O-2 cathode demonstrate the great enhancements of battery performances in terms of capacity, cycle retention, rate capability, and thermal properties. Pouch-type full cells assembled by combining the present cathodes with hard carbon anodes show good practical applicability, with an outstanding cycle retention of 77% over 400 cycles. The results of this study may open up a new avenue for designing and developing suitable transition metal oxide cathodes for high-performance sodium-ion batteries.
Keywords: NANI0.5MN0.5O2 CATHODE; LITHIUM; ELECTRODE